Prenatal ethanol exposure impairs sensory processing and habituation to visual stimuli, effects normalized by enrichment of postnatal environmental. (18th April 2022) - Wang, Ruixiang; Martin, Connor D.; Lei, Anna L.; Hausknecht, Kathryn A.; Turk, Marisa; Micov, Veronika; Kwarteng, Francis; Ishiwari, Keita; Oubraim, Saida; Wang, An‐Li; Richards, Jerry B.; Haj‐Dahmane, Samir; et al.
Abstract: Background: Individuals with fetal alcohol spectrum disorders (FASD) often show processing deficits in all sensory modalities. Using an operant light reinforcement model, we tested whether prenatal ethanol exposure (PE) alters operant responding to elicit a contingent sensory stimulus—light onset (turning on the light) and habituation to this behavior in rats. We also explored whether postnatal environmental enrichment could ameliorate PE‐induced deficits. Methods: Pregnant Sprague Dawley rats were gavaged twice/day with 0 or 3 g/kg/treatment ethanol (15% w/v) during gestational days 8–20, mimicking second‐trimester heavy PE in humans. The offspring were reared in a standard housing condition or an enriched condition. Adult male and female offspring underwent an operant light reinforcement experiment with either a short‐access or a long‐access procedure. A dishabituation test was also conducted to characterize the habituation process. Results: In the short‐access procedure, PE led to increased operant responding to the contingent light onset in both sexes reared in the standard housing condition. Such an effect was not observed in rats reared in enriched conditions due to an overall decrease in responding. Moreover, rats reared in enriched conditions showed greater short‐term habituation. In the long access procedure, PE rats showed increased responding and impaired long‐term habituation. The long‐access procedure facilitated both short‐term and long‐term habituation in control and PE rats. Conclusion: Prenatal ethanol exposure increases responding to contingent light onset and impairs the long‐term habituation process. The PE‐induced deficits were ameliorated by rearing in the enriched environment and increasing the duration and frequency of exposure to light onset. The PE‐induced effects are like increased sensation‐seeking, a subtype of sensory‐processing deficit that is often observed in individuals with FASD. Our findings could inform a suitable animal model for investigating the underlying mechanisms and possible intervention strategies for sensory deficits in FASD. Abstract : Individuals with fetal alcohol spectrum disorders (FASD) show sensory processing deficits including augmented sensation seeking. Using the operant light reinforcement paradigm in which rats poke holes to turn on the light, we found prenatal ethanol exposure increases responding to turning on the light and impairs its habituation, effects consistent with increased sensation seeking. Postnatal environmental enrichment or longer operant sessions significantly improve the above deficits. Our findings could inform a suitable animal model for investigating sensation seeking deficits in FASD.